Helmintos gastrointestinais de tartarugas-verdes (Chelonia mydas) recolhidas no litoral do Estado do Espírito Santo - Gomes, Moara Cuzzuo (2016)
All species of sea turtles are endangered to some degree and Chelonia mydas that has more coastal habits and are widely distributed along the Brazilian coast. There are several threats, mainly linked to human activities, and among the diseases, parasitism is considered a probable cause of illness and death. The aim was to evaluate the community of gastrointestinal helminths and perform the morphological characterization of your eggs in green turtles collected on the coast of the Espírito Santo, Brazil, from March to August 2015. A total of 36 juvenile C. mydas turtles were used, the entire gastrointestinal tract was removed and divided into three portions: esophagus / stomach, small intestine and large intestine. Each portion was inspected looking for parasites and the specimens found were separated macroscopically for subsequent permanent mounting. For each species found were determined the prevalence, mean intensity and mean abundance of species. For fecal evaluation, feces were processed according to the sedimentation technique and the eggs were found morphologically characterized and compared to those found in adult helminths. Of the 36 evaluated turtles, the prevalence of helminth was 94,44% (34/36), a total of 10,734 helminths were recovered. 18 species of trematodes belonging to four families were found. The average species richness was 4.29 ± 2.19. The most prevalent parasites were Cricocephalus albus, Metacetabulum invaginatum and Neoctangium travassosi, both 61.11% (22/36), followed by Pronocephalus obliquus 33.33% (12/36) and 30.55% with Glyphicephalus lobatus (11/36). Four different morphotypes were found and identified eggs in stool examinations and a large morphometric diversity of eggs in adult helminths.